A historical perspective on niche tourism: recreational trout fishing in South Africa - Rogerson, Christian M.; Rogerson, Jayne M. (Bulletin of Geography. Socio-economic Series, 2024)
Niche tourism is an important focus in current tourism scholarship. Although the international literature on niche tourism is relatively recent in origin it must be acknowledged that niche tourism is not a new phenomenon and that many types of niche tourism have a long history. The aim in this paper is to address a knowledge gap in current niche tourism literature by examining its under-researched past with a case study of recreational trout fishing in South Africa. Using archival sources this study documents the emergence of trout fishing in South Africa and gives historical insight into its origins as a niche form of rural tourism. The popularisation of recreational trout fishing was given an important boost by the infrastructure and agency of the South African Railways especially its publicity and marketing material. Enhanced automobilities and the emergence of early drive tourism, a by-product of improvements which occurred from the 1930s in South Africa’s road network, further boosted the growth of trout fishing as a niche in rural tourism.